2023
DOI: 10.1007/s40489-023-00407-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Children and Adolescents with ASD and ADHD: a Systematic Review

Rachele Lievore,
Giulia Crisci,
Irene C. Mammarella

Abstract: Children and adolescents with autism spectrum disorder (ASD) and attention deficit and hyperactivity disorder (ADHD) show difficulties in recognizing emotions. Similarities and differences between these two clinical groups’ emotion recognition (ER) have been little explored. This systematic review aims to summarize the results of comparative studies that included samples of cases with ASD and ADHD. A systematic search was conducted following PRISMA guidelines, and 24 papers were included. Behavioral, brain-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Some studies have identified a generalized face-emotion recognition deficit across all emotional facial expressions in autistic children (Lindner & Rosén, 2006;Lozier et al, 2014;Rump et al, 2009), whereas others revealed a lower performance for one or a subset of expressions, highlighting emotion-specific challenges mainly for negative emotions, which have variously included anger, fear, disgust, sadness, and surprise (see for example, Ashwin et al, 2007;Economides et al, 2020;Humphreys et al, 2007). Moreover, challenges with emotion recognition in ASD might also vary based on the type of measure (i.e., accuracy vs reaction times), task (i.e., verbal vs non-verbal), emotion complexity (i.e., basic vs complex emotions), processing (i.e., holistic vs featural), and stimuli (i.e., faces vs speech prosody) (for reviews and meta-analyses see, Leung et al, 2022;Lievore et al, 2023;Yeung, 2022). Overall, the large variability of findings on the topic denotes a literature gap which is incapable of establishing a clear framework; for this reason, it is essential to increase the evidence-based results on the study of FER in autism, by also embracing possible associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified a generalized face-emotion recognition deficit across all emotional facial expressions in autistic children (Lindner & Rosén, 2006;Lozier et al, 2014;Rump et al, 2009), whereas others revealed a lower performance for one or a subset of expressions, highlighting emotion-specific challenges mainly for negative emotions, which have variously included anger, fear, disgust, sadness, and surprise (see for example, Ashwin et al, 2007;Economides et al, 2020;Humphreys et al, 2007). Moreover, challenges with emotion recognition in ASD might also vary based on the type of measure (i.e., accuracy vs reaction times), task (i.e., verbal vs non-verbal), emotion complexity (i.e., basic vs complex emotions), processing (i.e., holistic vs featural), and stimuli (i.e., faces vs speech prosody) (for reviews and meta-analyses see, Leung et al, 2022;Lievore et al, 2023;Yeung, 2022). Overall, the large variability of findings on the topic denotes a literature gap which is incapable of establishing a clear framework; for this reason, it is essential to increase the evidence-based results on the study of FER in autism, by also embracing possible associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%